Plastic and terrestrial organic matter degradation by the humic lake microbiome continues throughout the seasons - Vesamäki, Jussi S.; Laine, Miikka B.; Nissinen, Riitta; Taipale, Sami J. (Wiley-Blackwell, 2025)
Boreal freshwaters go through four seasons, however, studies about the decomposition of terrestrial and plastic compounds often focus only on summer. We compared microbial decomposition of 13C-polyethylene, 13C-polystyrene, and 13C-plant litter (Typha latifolia) by determining the biochemical fate of the substrate carbon and identified the microbial decomposer taxa in humic lake waters in four seasons. For the first time, the annual decomposition rate including separated seasonal variation was calculated for microplastics and plant litter in the freshwater system. Polyethylene decomposition was not detected, whereas polystyrene and plant litter were degraded in all seasons. In winter, decomposition rates of polystyrene and plant litter were fivefold and fourfold slower than in summer, respectively. Carbon from each substrate was mainly respired in all seasons. Plant litter was utilized efficiently by various microbial groups, whereas polystyrene decomposition was limited to Alpha- and Gammaproteobacteria. The decomposition was not restricted only to the growth season, highlighting that the decomposition of both labile organic matter and extremely recalcitrant microplastics continues throughout the seasons.